A passive wall design to minimize building temperature swings for Algerian Saharan climate. (3rd October 2017) - Mokhtari, Fatiha; Loukarfi, Larbi; Chikhi, Mourad; Imessad, Khaled; Ait Messaoudene, Noureddine
Abstract : In this study, the effect of both high thermal insulation and high thermal mass are investigated numerically using TRNSYS simulation software under steady periodic conditions. This investigation is carried out for a high-energy efficiency home under the Saharan climate conditions of Bechar City. In order to perform this analysis and to achieve the best performance, several external wall configurations are proposed. These configurations are based on changing two aspects; walls construction materials using stabilized earth blocks and clay bricks, and the other one is insulating materials using polystyrene and a new biocomposite insulating material referenced as hemihydrate gypsum/date palm fibers available in Bechar City. The calibration of the model is performed through a comparative study of numerical temperature results with experimental data. Thermal characteristics such as indoor temperature, yearly heating and cooling loads, time lag, and decrement factor are determined for each configuration. The results show that good thermal performances are achieved by the stabilized earth blocks-hemihydrate gypsum/date palm fibers (wall 2) configuration. This configuration gives the lowest indoor temperature swings and yearly heating and cooling loads. Considering the cost analysis, the wall 2 configuration yields an affordable cost.